Pengaruh Program Stand Up Comedy Indonesia Kompas TV terhadap Perilaku Komika di Komunitas Stand Up Indo Surabaya - Febe Cruisita Geralda Runtuwaliam (LPPM Stikosa - AWS, 2018)
Kompas TV as one of the private television stations, by giving a new program in the form of competition, namely Stand Up Comedy Indonesia. With its existence that has been running for 8 sessions, Stand Up Comedy Indonesia is still popular with the Indonesian people as evidenced by the enthusiasm and interest of the public in auditioning. The problem formulation in this research is